Toward an Accurate Spectrophotometric Evaluation of the Efficiencies of Photocatalysts in Processes Involving Their Separation Using Nylon Membranes - Halema Al-Kandari (6316961) (2018)
Many works include the use of nylon membranes to separate the solid particles of photocatalysts from the photocatalytic reactors, before using spectrophotometers to evaluate the catalysts’ performance in the photocatalytic degradation of many pollutants. This might lead to significant errors due to the adsorption of some pollutants within the structure of the membranes during the filtration process used to separate the solid particles of the photocatalysts to get a clear filtrate. This, consequently, leads to incorrect calculations, which in turn are translated into false high photocatalytic efficiencies of the used catalysts. In this work, the authors study the interaction between nylon membrane filters and five different model compounds—phenol red, methylene blue, rhodamine B, rhodamine 6G, and phenol. The study reveals a significant interaction between the nylon membranes and both rhodamine B and phenol red. Other Information Published in: Catalysts License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/catal8120576